The Effects of Entrepreneurial Personality to Competitiveness and Corporate Image: A Study on Chocolate Agent Entrepreneurs - Chaniago, Harmon (International Review of Management and Marketing, 2020)
This study investigates the entrepreneur personalities of chocolate agents and their effect on competitiveness and corporate image. The object of the study is chocolate agent resellers which are spread throughout Indonesia. The total sample is 110 entrepreneurs who work as company agents. The method used is survey confirmatory method. From this research, seven entrepreneurial personalities that can increase competitiveness and corporate image are found. The practical implication is that companies' managerial need to set up criteria for agent recruitment and to be selective in choosing agents. The chosen agents must be trained continually to develop their personality traits such as the ability to think positively, develop leadership traits, be open-minded, have consciousness of the importance of business, be friendly, give good service, be independent, and be able to reach targets. Keywords: Entrepreneur Personality, Competitiveness, Corporate Image, Company Agents JEL Classifications: D41, D91, L26 DOI: https://doi.org/10.32479/irmm.9262